2021
DOI: 10.52113/mjas04/8.2/62
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Levels of Biochar in Some Soil Physical Properties and Growth Parameters of Oat (Avena sativa L.)

Abstract: A pots experiment was performed in the greenhouse of the College of Agriculture, University of Basrah in clay loam soil, to study the effect of the different levels of biochar on some soil physical properties (bulk density, total porosity, moisture content, mean weight diameter and saturated hydraulic conductivity) and some indicators of oat crop growth (height and dry weight of the plant). The experiment included the use of six different levels of biochar: B0 (control), B1 (1%), B2 (1.5%), B3 (2%), B4 (2.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…The Bulk soil density decreased significantly in treatments 1 and 2% for perlite and their values were 1.23 and 1.20 Mg m 3 , respectively, with a decrease of 9 and 11% in the sandy loam soil. Biochar significantly reduced the bulk density of clay soil and sandy loam, due to the decrease in the bulk density of the used biochar, which amounted to 0.34 Mg m 3 , and the decrease in the bulk density of perlite, which amounted to 0.50 Mg m 3 , and because of their high porosity, which is consistent with What was found by [3], and [15]. Table 3.…”
Section: Bulk Density (Mg M 3 )supporting
confidence: 89%
See 2 more Smart Citations
“…The Bulk soil density decreased significantly in treatments 1 and 2% for perlite and their values were 1.23 and 1.20 Mg m 3 , respectively, with a decrease of 9 and 11% in the sandy loam soil. Biochar significantly reduced the bulk density of clay soil and sandy loam, due to the decrease in the bulk density of the used biochar, which amounted to 0.34 Mg m 3 , and the decrease in the bulk density of perlite, which amounted to 0.50 Mg m 3 , and because of their high porosity, which is consistent with What was found by [3], and [15]. Table 3.…”
Section: Bulk Density (Mg M 3 )supporting
confidence: 89%
“…As for perlite percentages, the water conductivity increased when treated with 2% perlite, its value was 0.49 cmh -1 for the Clay loam soil with an increase of 65%, and the water conductivity increased when treated with 2% perlite and reached 2.09 cm hr -1 in the sandy loam soil with an increase of 35%. Biochar worked to increase the water conductivity values in the clay loam soil due to the decrease in the bulk soil density and the increase in its porosity and aggregations, and this is consistent with the findings of [3], while biochar reduced the water conductivity in the sandy loam soil, due to the low bulk density due to the high micropores, which must be filled before draining Water is under the influence of gravity, as found by [14]. The use of perlite led to an increase in water conductivity in the two soils, due to the decrease in the bulk density values and the increase in the moisture content values.…”
Section: Saturated Hydraulic Conductivity (Cm H -1 )supporting
confidence: 88%
See 1 more Smart Citation
“…Results in table (1) show the moral effect of adding biochar and organic fertilizer extract and their overlap in plant height values with moral differences, Note from the table to increase plant elevation IOP Publishing doi:10.1088/1755-1315/1262/8/082042 3 values while increasing levels of biochar , As the A3 transaction outperformed all transactions by registering the highest value of the plant's height of 109.48 cm, this results are consistent with that of [16] The addition of biochar to the soil has increased the rise of the oat plant. The results of table (1) show that there are moral differences in the levels of addition of organic fertilizer extract to the soil as the levels of B3 and B2 morally exceeded the plant's height by averages of 108.07 and 106.78 cm, respectively.…”
Section: Plant Height (Cm)supporting
confidence: 71%
“…Biochar is a porous organic carbon compound produced through the pyrolysis of biomass at temperatures ranging between 300-1000 degrees Celsius and under conditions of lack of oxygen. There are many studies that confirmed that adding it to the soil improves many IOP Publishing doi:10.1088/1755-1315/1262/8/082011 2 physical properties of the soil such as particle density, total porosity, soil moisture content, and soil hydraulic conductivity [4]. Perlite is a material resulting from heating silicon volcanic rocks from 900 to 1000 degrees Celsius [5].…”
Section: Introductionmentioning
confidence: 99%